Principles of Circulatory Support in a Potential Donor with Adequate Oxygenation at the Prehospital Stage: Review of International Protocols and Recommendations - Filimonova, I. V.; Goldovsky, B. M.; Potalov, S. O.; Serikov, K. V.; Semenova, T. O.; Korogod, S. M.; Filimonov, R. V.; Lelyuk, D. V. (Transplantation and artificial organs, 2020)
Objective. Study the issues of ensuring the vital functions of the organism of a potential donor at the prehospital stage in the structure of transplantology. In our work, an analysis of specialized literature and studies on the functioning of the body of a potential donor at the prehospital stage has been carried out. The complex of measures for the maintenance of the vital functions of the body of a deceased person is a more difficult task compared to carrying out standard intensive care in severely ill patients. At present, this amount of work is poorly studied and often condemned (including by colleagues) the workload for resuscitation department staff and heads of medical institutions. In recent years, experimental and clinical studies have been conducted on new alternative methods that should improve blood flow during cardiopulmonary resuscitation (CPR) and patient survival. Automated systems for compression of the chest, which do not require manual intervention, are developed, as well as the prevention of fatigue in persons who perform CPR. The automation of the execution of the compress allows the personnel to be freed, and helps the honey staff to pay attention to other tasks necessary to maintain the patient’s livelihood. Conclusions. Correct and well-organized organization of aid at the prehospital stage in the event of a sudden death of a person can significantly help not only the development of such a branch of medicine as transplantology, but also increase the percentage of successfully performed resuscitation measures.